Potential Chemoprotectants Platinum- Based Therapy with S-ligand Using ATP Bioluminescence Assay - AlOmari, Nohad A; Kasim Salih, Seema Mahmood Al-Haj; Pietrella , Donatella (International Journal of Psychosocial Rehabilitation, 2020)
The critical dose limiting side effect of cisplatin is nephrotoxicity; 20% of patients receiving a high dose of cisplatin have suffered from severe renal dysfunction; the ability to manage this induced toxicity is crucial for the success of chemotherapy. The concomitant administration of chemoprotective agents become an important approach in a platinum chemotherapy, the potential reversibility of Pt-S bonds in presence of other sulfur ligands suggests that certain Pt-bound sulfur ligand can be substituted by other sulfur nucleophiles, and Pt can be transferred between various S-containing molecules which form the chemical basis to alleviate the acute platinum toxicity using chemoprotectants. This research concerned with the cytotoxicity studies of already prepared new Pt(II) complexes with S-donor ligands, mesna and dimesna; using ATP bioluminescence assay against HeLa, BEAS-2B and A549. The best results were obtained with A549 cell line and were not differing significalnty from the contol (cisplatin), Our fininding sugggest that there are potenitainls in delivering the chemoprotection with acceptable cytotoxicity.